Upper limits on hydrogen halides in Jupiter from Cassini/CIRS observations - Fouchet, T; Orton, G; Irwin, P; Calcutt, S; Nixon, C (2004)
We have determined the following upper limits for the mole fraction of hydrogen halides in Jupiter's atmosphere from Cassini/CIRS observations: [HF] <2.7×10-11, [HCl] <2.3×10-9, [HBr]<1.0×10-9, [HI] <7.6×10-9. These limits are smaller than solar composition for HF and HCl, and support the halogens' condensation in ammonium salts predicted by thermochemical models for the upper jovian troposphere. © 2004 Published by Elsevier Inc.